2009
DOI: 10.1097/mao.0b013e31819bd7e6
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Results After Bilateral Cochlear Implantation in Adults

Abstract: Speech understanding in noise is improved with bilateral cochlear implantation with unambiguous evidence that the second implant expands the sound field for effective speech recognition. Communication in daily life is facilitated, as determined by the subjective Speech, Spatial and Qualities of Hearing Scale test. The correlation of the subjective and objective results confirms the practical benefits in daily activities. Although there was improvement with a second Cochlear implant even after a long implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
1
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(111 citation statements)
references
References 35 publications
8
98
1
4
Order By: Relevance
“…In this configuration and in a sound-treated room, SRM reaches only 3 to 5 dB (e.g., Litovsky et al, 2009). However, three studies have tested CI users in the symmetrical situation where speech and noise sources are placed at equal and opposite azimuths (645 or 660 ) Laske et al, 2009;Laszig et al, 2004). These studies demonstrated that with speech and noise sources separated by 90 or 120 , a head orientated midway between the sound sources could lead to a significant head-shadow benefit of bilateral over unilateral implantation (10 to 18 dB).…”
Section: Introductionmentioning
confidence: 99%
“…In this configuration and in a sound-treated room, SRM reaches only 3 to 5 dB (e.g., Litovsky et al, 2009). However, three studies have tested CI users in the symmetrical situation where speech and noise sources are placed at equal and opposite azimuths (645 or 660 ) Laske et al, 2009;Laszig et al, 2004). These studies demonstrated that with speech and noise sources separated by 90 or 120 , a head orientated midway between the sound sources could lead to a significant head-shadow benefit of bilateral over unilateral implantation (10 to 18 dB).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of speech intelligibility in noise has been a key focus in a considerable number of studies with adult bilateral cochlear implantees (e.g., Schön et al, 1999;van Hoesel and Clark, 1999;Gantz et al, 2002;Müller et al, 2002;Schön et al, 2002;Stark et al, 2002;Tyler et al, 2002;van Hoesel et al, 2002;Au et al, 2003;van Hoesel and Tyler, 2003;Dormann and Dahlstrom, 2004;Laszig et al, 2004;Schleich et al, 2004;Ramsden et al, 2005;Senn et al, 2005;Litovsky et al, 2006Litovsky et al, , 2009Ricketts et al, 2006;Tyler et al, 2006Tyler et al, , 2007Buss et al, 2008;Chan et al, 2008;Dunn et al, 2008;Zeitler et al, 2008;Eapen et al, 2009;Laske et al, 2009;Loizou et al, 2009;Koch et al, 2009;Mosnier et al, 2009). Despite variation in methodology and materials, it is generally the case that the largest speech intelligibility benefit from having two implants derives from the monaural effect of the headshadow at each ear, which allows the listener to attend the ear with the better signal-to-noise ratio (SNR) when target and interferers are spatially separated.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the SSQ scale explores aspects of hearing through 49 items organized into three subscales measuring: the capacity of the individual to listen to speech in different hearing contexts (Part 1 -speech hearing); localization of sound events for different directions, distances and movement (Part 2 -spatial hearing); and the listening experience in relation to segregating sounds, identification/ recognition, clarity and naturalness, musical perception and listening effort; (Part 3 -qualities of hearing) (5) . In the international literature, there are studies that apply the SSQ in different contexts investigating hearing loss and its impact (6,7,8,9) . Recently, in Brazil, SSQ 49 version 5.6 was translated and culturally adapted to Brazilian Portuguese and is currently undergoing the process of validation (10) .…”
Section: Introductionmentioning
confidence: 99%